2012
DOI: 10.4103/0972-0707.94591
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial of cold lateral compaction with Obtura II technique in root canal obturation

Abstract: Introduction:The purpose of obturation of the prepared root canal space is to prevent coronal leakage and bacterial contamination and to seal the apex from the periapical tissue fluids. Cold lateral technique has been considered to be a gold standard, however considering its limitations various thermoplasticized gutta-percha techniques have been recommended. This study compares radiographic quality of obturation in molar teeth, obturated with cold lateral condensation and thermoplasticized injectable gutta-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Cold lateral condensation technique and Obtura II have also compared in clinical studies. Ansari et al (18) concluded that there is no significant difference between these two techniques regarding voids and apical termination.…”
Section: Discussionmentioning
confidence: 99%
“…Cold lateral condensation technique and Obtura II have also compared in clinical studies. Ansari et al (18) concluded that there is no significant difference between these two techniques regarding voids and apical termination.…”
Section: Discussionmentioning
confidence: 99%
“…1 Lateral compaction does not meet the requirement of providing homogeneous sealing of the root canal, unlike the warm vertical compaction technique, which provides homogeneous sealing allowing adaptation of material to the walls, and even sealing root canal irregularities. 5,6 The cold single-cone technique, on the contrary, is being widely used nowadays due to its simplicity and low cost, even though it does not provide a threedimensional sealing of the root canal, in contrast to the evidence, which has demonstrated that this technique has high failure rates due to poor sealing. [7][8][9][10] Dye penetration and microbial filtration are the two most common methods to evaluate microleakage of endodontic obturations, 11 but microbial filtration is the most relevant method, since it fits clinical conditions.…”
Section: Introductionmentioning
confidence: 94%
“…1 La compactación lateral no cumple el requisito de generar un sellado homogéneo del conducto radicular, contrario a la técnica de compactación vertical caliente, la cual logra un sellado homogéneo que permite la adaptación del material a las paredes, sellando incluso las irregularidades en el conducto. 5,6 La técnica de cono único en frío, por el contrario, está siendo ampliamente usada en nuestro medio debido a su facilidad y bajos costos, sin importar que se logre o no el sellado tridimensional del conducto radicular, lo cual va en contraposición a la evidencia, que ha demostrado que esta técnica presenta altos índices de fracaso debido a su falta de sellado. [7][8][9][10] La filtración con tintes y la filtración microbiana son los dos métodos más comunes para evaluar la microfiltración de obturaciones endodónti-cas, 11 pero la filtración microbiana es el método más relevante, ya que se ajusta a las condiciones clínicas.…”
Section: Introductionunclassified
“…[1] We would like to share some comments and observations about the said manuscript with you and the readers of the journal.…”
mentioning
confidence: 99%
“…Even in the text of results on p.159; left column, second paragraph, it was mentioned as “there were 53 cases (83.33%) with postoperative voids and 7 (11.67%) had no postoperative voids.”[1] This in actual should be in reverse.…”
mentioning
confidence: 99%